Dealing with Past Colonial Conflicts: How Perceived Characteristics of the Victimized Outgroup Can Influence the Experience of Group-Based Guilt - Figueiredo, Ana Mateus; Doosje, Bertjan; Valentim, Joaquim Pires; Zebel, Sven (International Journal of Conflict and Violence (IJCV), 2010)
An examination of potential outgroup-focused predictors of group-based guilt relating to past colonial conflicts involving Portugal and the Netherlands, specifically, the role of the perceptions of the ingroup towards the victimized outgroup, as well as on outgroup identification and meta-perceptions (i.e. the ingroup's beliefs regarding the outgroup's perceptions of it). Using Structural Equation Modeling in a Portuguese sample (N = 178) and a Dutch sample (N = 157), we found that the experience of group-based guilt due to colonial conflicts can be positively predicted by outgroup perceptions and outgroup identification (Dutch sample only). Meta-perceptions were a negative predictor of group-based guilt (Dutch sample only). Furthermore, our results show that group-based guilt is positively associated with compensatory behavioral intentions and perceived importance of remembering past colonial conflicts. Results point to the important role of outgroup-focused variables in shaping group-based guilt experiences relating to past conflicts between groups. The findings suggest possible avenues of further research and ways to improve intergroup relations following conflict.